Multiculturalism and Innovation at Workplace: A Bank Employee’s Perspective - Shrestha, Raksha; Pathak, Anubhav; Shrestha, Jagdish; Adhikari, Somit; Nath, Nilam; Parajuli, Suman Kamal (International Journal of Atharva, 2026)
Having people from different cultures at work can bring new ideas and creativity. Understanding how employees see multiculturalism and its effect on innovation is important, especially in banks where teamwork and problem-solving are key. This study used a survey to gather opinions from 100 employees at NIC Asia Bank, Global IME Bank, and Kumari Bank. The participants included managers, staff, and interns. The study looked at how communication, culture, ethnicity, and leadership relate to innovation, and the data were analyzed using basic statistical methods. Employees generally had positive views about multiculturalism. Ethnicity, leadership, and culture were strongly linked to innovation, while communication had a smaller impact. The analysis showed that ethnic diversity and supportive leadership were the strongest factors in encouraging new ideas at work. Multicultural practices help create innovative workplaces. Focusing on respecting different ethnic backgrounds and having inclusive leadership can boost creativity. While culture helps, communication alone may not directly increase innovation.